Respuesta :

Answer:

The answer is option A

Step-by-step explanation:

f(x) = (x+1)³ + 4

To find f-¹(x) equate f(x) to y

That's

y = (x+1)³ + 4

Next interchange the terms x becomes y and y becomes x

That's

x = ( y+1)³ + 4

Make y the subject

(y+1)³ = x - 4

Find the cube root of both sides

That's

[tex]y + 1 = \sqrt[3]{x - 4} [/tex]

Send 1 to the right side of the equation

That's

[tex]y = \sqrt[3]{x - 4} - 1[/tex]

So we have the final answer as

[tex]f ^{ - 1} (x) = \sqrt[3]{x - 4} - 1[/tex]

Hope this helps you

Answer:

option 1

Step-by-step explanation:

f(x)=(x+1)³+4

to find the inverse interchange the variable and solve for y

inverse f(x)=(y+1)³+4

x=(y+1)³+4

x-4=(y+1)³

y+1=∛x-4

y=∛x-4 -1